The Influence of Managerial Support and ICT Facility Availability on Learning Effectiveness Through Teachers' Digital Competence in Public Senior High Schools in Pandeglang Regency - Nono Suhada (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Purpose: This study aims to examine the effect of managerial support and the availability of information and communication technology (ICT) facilities on learning effectiveness, both directly and through teacher digital competence as a mediating variable, among teachers at State Senior High Schools (SMA Negeri) in Pandeglang Regency, Banten Province. Research Methodology: This research used a quantitative correlational design. Data were collected from 161 permanent teachers across five State Senior High Schools in Pandeglang Regency, selected through proportionate stratified random sampling from a population of 269 teachers. A structured questionnaire using a five point Likert scale was distributed to measure managerial support, ICT facility availability, teacher digital competence, and learning effectiveness. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through bootstrap resampling of 5,000 iterations. Results: The findings show that managerial support and ICT facility availability each have a positive and significant effect on learning effectiveness and on teacher digital competence. Teacher digital competence also has a positive and significant effect on learning effectiveness and partially mediates the relationship between the two exogenous variables and learning effectiveness. The structural model explains 69.1 percent of the variance in teacher digital competence and 73.4 percent of the variance in learning effectiveness, with a good model fit (SRMR = 0.036). Conclusions: Managerial support and ICT facilities jointly strengthen learning effectiveness, and this influence is reinforced when it passes through improvements in teacher digital competence, which functions as the central bridge connecting institutional support and technological resources with classroom quality. Limitations: This study used a cross-sectional design with self-reported data from a sample limited to five public schools in one regency, so the findings cannot yet be generalized broadly to other regions or school types. Contribution: This study offers practical input for school principals and education policy makers in Pandeglang Regency and similar regions in designing managerial support strategies and ICT facility investments that are directed at strengthening teacher digital competence as a key lever for improving learning effectiveness..